Impact of twin shield tunnel construction on the deformation of bridge pile groups beneath multiple bridges: a case study - Deng, Lan; Liu, Jizhixian; Huang, Chenze; Yang, Shan; Huang, Junzhou; Wu, Cai (Frontiers in Built Environment, 2025)
With the rapid advancement of urbanization, the demand for efficient transportation networks, particularly for shield tunnels, has been rising. However, tunnel excavation significantly affects the surrounding soil and elevated bridge pile foundations, potentially leading to complex mechanical responses and safety risks for structures. Although prior studies have examined the impact of tunnels on pile foundations, systematic research on the deformation patterns of pile groups remains limited. Based on the case of the Zhengzhou Metro Line five crossing beneath the Shijiazhuang-Wuhan High-Speed Railway Bridge, this study uses three-dimensional finite element numerical simulations and field monitoring data to analyze the effects of tunnel excavation on bridge pile groups. The results reveal that: (1) For single-track excavation, the maximum horizontal displacement of the pile group increases to 1.587 mm, while for double-track excavation, it reaches 1.813 mm, with pile settlement increases to a maximum of 5.03 mm; (2) The maximum settlement and horizontal deformation of the bridge piles show a negative correlation with the minimum spacing between piles, with deformation increasing exponentially as the spacing decreases; (3) The excavation process at all stages affects the piers, with initial maximum settlement increasing from 0.787 mm to 3.569 mm, a growth rate of 201.91%, and maximum horizontal displacement reaching 1.576 mm. The final settlement and horizontal displacement are 5.171 mm and 1.770 mm, respectively; (4) Field monitoring and numerical analysis indicate that bridge piles in close proximity (e.g., piles 17#, 18#, 35#) are more significantly impacted by the tunnel, with maximum settlement and inclination reaching 4.5 mm and 0.008, while more distant piles (e.g., piles 16#, 20#, 34#) are less affected. These findings offer important insights for the design and construction of urban infrastructure projects, contributing to the sustainable development of cities by ensuring the safety and stability of built environment within rapidly evolving urban social spaces.